2001
DOI: 10.1080/14622200020032105
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing concerns about post-cessation weight gain: results from a national survey of women smokers

Abstract: Differences among adult women smokers with differing levels of concern about post-cessation weight gain were investigated in a national random-digit-dialing survey. To avoid defining weight concerns in terms of possible etiologies or contributory factors, respondents were stratified using a single item querying concern about post-cessation weight gain; 39% described themselves as very concerned (VC), 28% as somewhat concerned (SC), and 33% as not concerned (NC). Significant between-groups differences were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
112
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(118 citation statements)
references
References 65 publications
3
112
1
2
Order By: Relevance
“…5 The increase in body weight by age has been found to be lower among smokers than among nonsmokers, 6 and body weight seems to be highest in former, lowest in current and medium in never smokers. 1,7,8 Weight gain attributed to smoking cessation was positively related to the number of cigarettes smoked per day (cpd) in a study with men at high risk of death from coronary heart disease.…”
Section: Introductionmentioning
confidence: 97%
“…5 The increase in body weight by age has been found to be lower among smokers than among nonsmokers, 6 and body weight seems to be highest in former, lowest in current and medium in never smokers. 1,7,8 Weight gain attributed to smoking cessation was positively related to the number of cigarettes smoked per day (cpd) in a study with men at high risk of death from coronary heart disease.…”
Section: Introductionmentioning
confidence: 97%
“…6 However, weight gain after quitting is often given as a reason for not stopping smoking, especially among women. [6][7][8] This is increasingly well-known by the population at large and has been dealt with in clinical practice after carrying out cardiovascular prevention. Most studies have observed that there is indeed an increase in weight after stopping smoking, although the weight gain varied between them.…”
Section: Smoking Assessmentmentioning
confidence: 99%
“…[3][4][5] Smokers with depression are more likely to relapse from a quit attempt, have higher nicotine dependence, suffer negative mood symptoms from withdrawal, and suffer greater smoking-related morbidity and mortality than the general population of smokers. [6][7][8][9][10][11][12] For the general population, effective smoking cessation interventions include nicotine replacement therapy (NRT), 13 antidepressants bupropion and nortriptyline, 14 nicotine receptor partial agonists varenicline, 15 and smoking cessation counseling. [16][17][18] Pharmacological and behavioral strategies increase the likelihood of successful quits attempt by 1.5 to 2 times compared to placebo or usual care.…”
mentioning
confidence: 99%